Implementation of Smart Management in Optimizing Digital Marketing in MSMES By Bumdesa Sido Makmur - Arista Pratama; Mohammad Idhom; Alfiandi Imam Mawardi; Silvia Ayu Ningtyas (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The development of information and communication technology opens up great opportunities for MSMEs to expand the market through digital platforms. BUMDESa Sido Makmur as a village-owned enterprise has a strategic role in supporting the economic potential of MSMEs through empowerment programs. The MSME products by BUMDESa Sido Makmur have good quality and wide market potential, but are still hampered by limited marketing access and inadequate promotional strategies. This community service activity aims to implement Smart Management through the use of the Shopee and Linktree platforms in optimizing digital marketing for MSMEs by BUMDESa Sido Makmur. This training method involves two main stages, namely a smart management approach through Shopee to improve the quality of data-based marketing and the creation of Linktree to improve the connectivity and accessibility of product information. The results of this training show that the integration of Smart Management with the Shopee and Linktree platforms can have a great positive impact on the digital marketing of MSMEs by BUMDESa Sido Makmur.